THIN COCONUT COMMOMOGRAPHY FOR DETERMINATION OF HEARTIDINE IN ORANGE OF ORANGE FROM ORANGE - Sri Handayani; Sunarto Sunarto; Susila Kristianingrum (Jurnal Penelitian Saintek, 2005)
This   research   with   the   title   Thin   Layer   Chromatography  for Determination of Hesperidins Content in Orange Peel has been done in organic chemistry laboratory. The aim of this research is to select the solvent mix for  the best hesperidins standard peak result and to determinate the content (in relative percentage) of some orange peel. Hesperidins isolation from  orange peel conduct by soaks the orange peel piece  in f 0% Calcium hydroxide solution for  a night in room temperature.    The   mixture   than  jiltered    and   neutralized   with hydrochloric acid to obtain hesperidins contain filtrate.  Hesperidins analyzed   by   thin   layer   chromatography.    Characterization   of hesperidins did by compare the sample chromatogram with standard chromatogram.  The yield  (in  relative  percentage)   determinate  by  compare the sample peak area with hesperidins standard peak area. The solvent  mix  selected  before  by  attempt  some  solvent  mix for eludate hesperidins standard solution. The result of this research shown that hesperidins can analyzed using thin   layer   chromatography   method.   with   the   best  solvent   was chloroform:  methanol mixture (2 : 3). Hesperidins content in extract solution of some strain orange peel  is; Baby Egypt 0, f 380%, Baby Pacitan 0,0615%, Mandarin Lokam 0,0018%, Santang 0,0049%, and Sunkist  Nevel 0,0360%.  The hesperidins  content  in orange peel  of Mandarin Pakistan, Medan super, Nipis, Sunkist,  Peras, and Purut was 0,0000. The hesperidins content in these orange peel was too low to be detected